Amino-functionalized mesoporous silica based polyethersulfone–polyvinylpyrrolidone composite membranes for elevated temperature proton exchange membrane fuel cells. Issue 89 (12th September 2016) - Zhang, Jin; Lu, Shanfu; Zhu, Haijin; Chen, Kongfa; Xiang, Yan; Liu, Jian; Forsyth, Maria; Jiang, San Ping
Abstract : It is important to find alternative membranes to the state-of-the-art polybenzimidazole based high temperature proton exchange membranes with high proton conductivity at elevated temperature but with simple synthesis procedures. Abstract : It is important to find alternative membranes to the state-of-the-art polybenzimidazole based high temperature proton exchange membranes with high proton conductivity at elevated temperature but with simple synthesis procedures. In this work, inorganic–organic nanostructured hybrid membranes are developed based on a polyethersulfone–polyvinylpyrrolidone (PES–PVP) polymeric matrix with hollow mesoporous silica (HMS), amino-functionalized hollow mesoporous silica (NH2 -HMS) and amino-functionalized mesoporous silica (NH2 -meso-silica). The composite membranes show a significant increase in proton conductivity and a decrease in the activation energy for proton diffusion in comparison with the phosphoric acid (H3 PO4, PA) doped PES–PVP membrane. And the composite membrane with NH2 -HMS shows the best performance under the conditions in this study, achieving the highest proton conductivity of 1.52 × 10 −1 S cm −1 and highest peak power density of 480 mW cm −2 at 180 °C under anhydrous conditions, which is 92.7% higher than that of the PA doped PES–PVP membrane at identical conditions. Such enhancement results from the facilitated proton transportation in the ordered mesoporous channels via the hydrogen bond between the –NH2 groups and H3 PO4 . The high water retention capability of silica materials with a hollow structure also contributes to the decrease of the activation of proton diffusion. Consequently, the results show promising potential of the NH2 -HMS based PES–PVP composite membrane for the elevated temperature proton exchange membrane fuel cells.